Hubungan Antara Pengelolaan Sumber Daya Manusia dalam Organisasi dengan Komitmen Karyawan pada Dinas Ketenagakerjaan dan Transmigrasi Sijunjung - Novella Rovitia; Oktaviola H.; Rahma Septia Sari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
In an increasingly competitive business situation, companies need employees who have a high commitment to the organization. Allen and Meyer (1990) stated that commitment to an organization is displayed in the components of affective commitment, rational commitment and nomative commitment. From several studies it has been proven that work experience has quite a big influence on employee commitment to the organization. This research will look at the contribution of human resource management as a form of work experience to employee commitment to the organization. What is meant by human resource management is a series of processes, applications and evaluations of the utilization and actualization of human resources in order to optimize the performance and contribution of human resources in achieving company goals. The contribution that will be seen is the contribution of human resource management in the form of employee perceptions of human resource management. As well as discrepancies in employee expectations and perceptions of human resource management. In particular, human resource management will be seen from the functions of managing employee development, managing work assessment, and management.